Structural characteristics of the KPR-CBR triple-junction inferred from gravity and magnetic interpretations, Philippine Sea Plate - Lu-ning Shang; Pan-feng Li; Run-lin Du; Feng-long Bai; Gang Hu; Wen-chao Lü; Xia Li; Xi Mei; Tian-yu Zhang; Hou-zhen Cao; Jing-yi Cong; Xian-yao Shi (China Geology, 2021)
The intersection of the Kyushu-Palau Ridge (KPR) and the Central Basin Rift (CBR) of the West Philippine Basin (WPB) is a relic of a trench-trench-rift (TTR) type triple-junction, which preserves some pivotal information on the cessation of the seafloor spreading of the WPB, the emplacement and disintegration of the proto-Izu-Bonin-Mariana (IBM) Arc, and the transition from initial rifting to steady-state spreading of the Parece Vela Basin (PVB). However, the structural characteristics of this triple-junction have not been thoroughly understood. In this paper, using the newly acquired multi-beam bathymetric, gravity, and magnetic data obtained by the Qingdao Institute of Marine Geology, China Geological Survey, the authors depict the topographic, gravity, and magnetic characteristics of the triple-junction and adjacent region. Calculations including the upward continuations and total horizontal derivatives of gravity anomaly are also performed to highlight the major structural features and discontinuities. Based on these works, the morphological and structural features and their formation mechanisms are analyzed. The results show that the last episode amagmatic extension along the CBR led to the formation of a deep rift valley, which extends eastward and incised the KPR. The morphological and structural fabrics of the KPR near and to the south of the triple-junction are consistent with those of the western PVB, manifesting as a series of NNE-SSW- and N-S-trending ridges and troughs, which were produced by the extensional faults associated with the initial rifting of the PVB. The superposition of the above two reasons induced the prominent discontinuity of the KPR in deep and shallow crustal structures between 15°N–15°30′N and 13°30′N–14°N. Combined with previous authors’ results, we propose that the stress produced by the early spreading of the PVB transmitted westward and promoted the final stage amagmatic extension of the CBR. The eastward propagation of the CBR destroyed the KPR, of which the magmatism had decayed or ceased at that time. The destruction mechanism of the KPR associated with the rifting of the PVB varies along strike the KPR. Adjacent to the triple-junction, the KPR was destroyed mainly due to the oblique intersection of the PVB rifting center. Whereas south of the triple-junction, the KPR was destroyed by the E-W-directional extensional faulting on its whole width.©2021 China Geology Editorial Office.